Contribution of Islamic Capital Market to National Capital Market - Dini Selasi; Muzayyanah Muzayyanah; Itat Tatmimah; Fitriya Sari; Rini Indriyani (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
Investing in the Islamic capital market has two objectives, namely by continuing to search for the world but not leaving the hereafter, namely by maintaining the satisfaction because it has been screened and supervised by OJK, DSN MUI. This study uses qualitative research methods, using secondary data, the analysis is carried out at the time of collecting data and when the data has been collected so as to get a solution and draw conclusions. The results obtained show that there is a high contribution from the Islamic capital market to the development of the national capital market through developments in Islamic capital market instruments such as Islamic stocks, corporate sukuk and state Islamic securities as well as through Islamic mutual funds which provide positive values ​​for the development of the national capital market.